Ruang Publik dan Kota Berkelanjutan: Strategi Pemerintah Kota Surabaya Mencapai Sustainable Development Goals (SDGs) - Trifita, Amjad; Amaliyah, Ridha (Global and Policy Journal of International Relations, 2020)
ABSTRACTThe research aims to analyze the strategy of the government of Surabaya as one of Indonesia’s metropolitan cities in manifesting sustainable city as mandated by United Nations on Sustainable Development Goals (SDGs) 2030 Vision. The SDGs commitement of sustainable city and society becomes a strong encouragement for local goverments around the world to play its role in realizing the agenda. The research is conducted using descriptive quantitative method and supported by various literatures as well as interviews of stakeholders. By focusing the strategy implemented in 2016-2019, the local government of Surabaya and United Cities and Local Governments Asia Pacific (UCLG ASPAC) initiates Global Public Space Programme. This research found that the public space project is carried out through 3 (three) strategies: (1) partnerships in the field of urban planning; (2) the use of Minecraft games in public space design; and implementation of the Global Public Space Program pilot project in three locations, which are Ketandan, Keputih and Tanah Kali Kedinding.Key Words: public space, sustainable city, Surabaya, Sustainable Development GoalsPenelitian ini bertujuan untuk menganalisis strategi pemerintah kota Surabaya sebagai salah satu kota metropolitan di Indonesia mewujudkan kota berkelanjutan sebagaimana diamanatkan oleh Perserikatan Bangsa-bangsa dalam Sustainable Development Goals (SDGs) 2030 Vision. Komitmen SDGs menjadi dorongan kuat bagi pemerintah daerah di seluruh dunia untuk memainkan perannya dalam mewujudkan agenda dimaksud. Tulisan ini berfokus pada metode kualitatif deskriptif yang disertai dukungan data literatur dan wawancara para pemangku kepentingan. Dengan menekankan pada pelaksanaan strategi di tahun 2016-2019, pemerintah kota Surabaya bekerjasama dengan United Cities and Local Governments Asia Pacific (UCLG ASPAC) menginisiasi pelaksanaan Global Public Space Programme. Strategi yang telah ditempuh pemerintah kota Surabaya adalah dengan (1) pembentukan kemitraan di bidang tata kelola kota, (2) penggunaan permainan Minecraft untuk desain tata kota, dan (3) menjalankan proyek nyata ruang publik di tiga titik strategis, yakni kampung Ketandan, Keputih, dan Tanah Kali Kedinding.Kata-Kata Kunci: ruang publik, kota berkelanjutan, Surabaya, Sustainable Development Goals